Amino Acid Mutations in Hemagglutinin-Neuraminidase Enhance the Virulence and Pathogenicity of the Genotype III Newcastle Disease Vaccine Strain After Intravenous Inoculation - Lu, Xiaolong; Liu, Xiaowen; Song, Qingqing; Wang, Xiaoquan; Hu, Shunlin; Liu, Xiufan (Frontiers in Veterinary Science, 2022)
Newcastle disease virus (NDV), the causative agent that generally causes severe disease in poultry, continues to mutate and has thus evolved into 21 genotypes. We previously isolated a velogenic genotype III NDV JS/7/05/Ch that evolved from the vaccine strain Mukteswar, accompanying by amino acid mutations in Hemagglutinin-Neuraminidase (HN). Here, we sought to investigate the role of the mutant HN protein in NDV virulence. The HN genes of Mukteswar and JS/7/05/Ch were replaced reciprocally via reverse genetics, yielding two recombinant viruses rJS/MHN and rMu/JHN, respectively. rMu/JHN, in which the endogenous HN protein was replaced with the HN protein of JS/7/05/Ch, had a higher intravenous pathogenicity index (IVPI) value in chickens. Moreover, dual aa mutations (A494D and E495K from JS/7/05/Ch-type HN) were introduced into the HN protein of Mukteswar to generate the recombinant virus rMukHN494+495JS. This virus showed an equivalent IVPI value to that of rJS/7/05/Ch (generated from parental JS/7/05/Ch via reverse genetics). In vitro and in vivo assays further showed that A494D and E495K in HN induced antigenic changes, a higher replication level and a more intense inflammatory response. Taken together, these findings indicate that aa mutations in HN are crucial for the virulence of the genotype III Newcastle disease (ND) vaccine strain after intravenous inoculation. Our study further highlights that close surveillance is needed to monitor the genetic variation of ND vaccine strains.